The reproductive potential and importance of key management aspects for successful Calluna vulgaris rejuvenation on abandoned Continental heaths. Issue 7 (27th February 2017) - Henning, Katrin; von Oheimb, Goddert; Härdtle, Werner; Fichtner, Andreas; Tischew, Sabine
Abstract: The abandonment of traditional pastoralism as well as the use of heath areas for military purposes has had a major impact on dry heaths in the Continental biogeographical region of Europe, causing severe degradation of its key species Calluna vulgaris (L.) HULL. The reproductive potential of this species in a Continental climate is assumed to be low, although there is yet no observational or experimental evidence for this. More knowledge is also needed about cost‐effective and sustainable measures to restore abandoned dry heaths in this biogeographical region, because traditional management options are often too expensive (e.g., sod‐cutting) or restricted due to environmental laws and the danger of unexploded ammunition (e.g., burning). Using as an example an 800 ha Continental heathland in Germany that has been abandoned for about two decades, we studied the reproductive potential (seed production, soil seed bank, and germination ability) of degenerate C. vulgaris stands. In addition, we conducted a comprehensive field experiment to test the effects of low‐intensity, year‐round grazing by Heck cattle and Konik horses as well as one‐time mowing and patchy exposure of bare soil on the generative rejuvenation (i.e., recruitment and survival) of degenerate C. vulgaris stands over 3 years. We used generalized linear mixed models for statistical analyses. Seed production of degenerate C. vulgaris stands was high as well as the germination ability of their seeds, being similar to Atlantic heathlands. However, soil seed‐bank densities were lower than those found in managed or abandoned Atlantic heaths. Overall seedling recruitment in the field was considerably lower in comparison with Atlantic heaths. Low‐intensity grazing or one‐time mowing did not induce a substantial increase in C. vulgaris recruitment, whereas an additional one‐time creation of bare soil patches or the one‐time creation of bare soil without subsequent management significantly facilitated seedling recruitment and survival in the first year. However, from the second year on, the positive effect of the creation of bare soil without subsequent management was no longer present. In the third year, survival of juveniles was significantly supported by low‐intensity grazing in combination with shallow soil disturbances as well as in combination with one‐time mowing and shallow soil disturbances, whereas mowing alone resulted in marginally significant lower survival. The extremely low seedling recruitment requires a careful choice of suitable management measures to promote the survival of sufficient numbers of Calluna individuals. Therefore, we recommend low‐intensity grazing with free‐ranging robust breeds and the combination of this with one‐time mowing as an effective means of supporting generative rejuvenation of C. vulgaris in degraded heaths. However, at the beginning of the restoration process, the creation of bare soil patches for seedling recruitment is crucial. For implementation into practice, we present different strategies to enhance the proportion of bare soil after long‐term abandonment of heaths when traditional management options are no longer feasible. Abstract : This study is the first to systematically determine the reproductive potential (i.e., number of produced seeds, soil seed bank content, germination ability of seeds) of degenerate Calluna vulgaris stands and the effects of single and combined management options on the generative rejuvenation of C. vulgaris to successfully restore long‐term abandoned, dry heaths in the Continental biogeographical region. Our study provides evidence that after long‐term management abandonment, seed production of degenerate Calluna stands and the germination ability of seeds proved to be high, whereas the soil seed bank is considerably reduced probably due to the dry conditions in the Continental region. Over the long term, low‐intensity grazing with free‐ranging robust breeds and the combination with one‐time mowing at the beginning of the restoration process is an effective means of supporting the generative rejuvenation of this key plant species in degraded Continental heaths.